2012
DOI: 10.1111/j.1365-2923.2012.04331.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of longitudinal integrated clinical placements for students, clinicians and society

Abstract: Longitudinal integrated clerkships are now recognised as representing credible and effective pedagogical alternatives to TBRs in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
252
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(270 citation statements)
references
References 72 publications
11
252
1
2
Order By: Relevance
“…Hereby, we found that both the non-LIC clinic attachments (50.0% of LCPs in our study) and LICs (26.5% of LCPs) name primary care exposure and recruitment as explicit goals significantly more often than non-LIC longitudinal patient attachment programs ( P  = .05 and P  = .02 respectively). These findings connect to outcomes in the literature demonstrating that LICs effectively support the primary care workforce [11,19,40,41]. We also consider these findings in the context of earlier studies demonstrating that 95% of students seeking primary care careers ‘desire for longitudinal patient care opportunities’ [42, p. 324].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Hereby, we found that both the non-LIC clinic attachments (50.0% of LCPs in our study) and LICs (26.5% of LCPs) name primary care exposure and recruitment as explicit goals significantly more often than non-LIC longitudinal patient attachment programs ( P  = .05 and P  = .02 respectively). These findings connect to outcomes in the literature demonstrating that LICs effectively support the primary care workforce [11,19,40,41]. We also consider these findings in the context of earlier studies demonstrating that 95% of students seeking primary care careers ‘desire for longitudinal patient care opportunities’ [42, p. 324].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, 73.5% of programs offered longitudinal structures with LIC-like elements but did not meet the criterion of the international research definition of an LIC that states LICs must ‘meet the majority of the academic year’s core clinical competencies across multiple disciplines simultaneously’ [15,16,18,19]. By using a broader definition of LCPs, our study characterizes longitudinal programs which would have been excluded under stricter criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations